Profitability analysis of commercial chemical and biological crop products among farm households in agroecological zones of West Africa - Bamire, A.; Abaidoo, Robert C.; Jemo, M.; Abdoulaye, Tahirou; Yusuf, A.A.; Nwoke, C. (Academic Journals, 2012)
This paper evaluates the costs and returns incurred by the use of chemical and biological crop products among households in five selected Compro communities in the derived, Southern Guinea, Northern Guinea, Sudan and Sahel Savanna agro-ecological zones (AEZs) in West Africa. Sixty households were randomly selected in each of the communities to give a total of 300 households. Data were collected on the characteristics of the chemical products, households’ socio-economic variables such as age and education, as well as, on farm input and output quantities and prices in the 2009/2010 periods using a pre-tested questionnaire. Data were analyzed with descriptive statistics and budgetary techniques. The Results obtained show a male dominant, fairly literate farming household, with small landholdings (comprising mainly cereal and legume fields) that are predominantly inherited and located far away from the homestead. Inorganic fertilizers, organic manure, improved seeds and pesticides are known as commercial inputs/ products used on farmers’ fields, while agrolizer, apron plus and boost extra are the emerging products. The average quantity of inputs applied varied across the zones. The total quantity of inorganic fertilizer applied on the fields was highest in the NGS (924 kg) and lowest in the Sudan (676 kg). However, fertilizer application per hectare by respondents was below recommended dosages across the zones. The emerging chemical inputs (Agrolizer, Boost Extra and Apron Plus) were used only in Compro communities in the derived savanna (DS) and southern guinea savanna (SGS) by a small number of households. The results obtained from budgetary analysis show that gross margin per hectare was highest in the SGS ($ 254) where the emerging inputs were used by 41.7% of the households and lowest in the Sahel ($ 76). Organic fertilizer was used only in small quantities in the AEZs.Total variable costs accounted for more than 30% of revenue generated, and labour and fertilizer accounted for the highest percentage of these costs. The study concludes that promoting the emerging chemical inputs through increased accessibility and farmers’ training on their appropriate agronomic use would increase farmers’ income generating potentials for sustainable crop production across the AEZs.